The Influence of Interest Rates and Inflation on the Yield to Maturity of Government Bonds Listed on the Indonesia Stock Exchange for the 2019-2021 Period - Syayidati Alfi Zahroh; Hartono; Yuliasnita Verlandes (International Journal of Management and Business Economics, 2023)
This research aims at determining the impact of interest rates and inflation on government bond yields to maturity. This type of research using quantitative method. Non-probability sampling technique with kind of saturated samples was used for the selection of research samples. The population of this research is government bond with fixed series code listed on the Indonesia Stock Exchange in 2019-2021.The analytical method used by multiple linear regression analysis method is done by SPSS 22. One of the conditions must use the classic assumption test to get a good regression. This study uses secondary data obtained from the Indonesia Stock Exchange. This study uses quarterly data from 2019-2021. The result of this research is that interest rates and inflation together affect bond yields to maturity. Interest rate and inflation variables has positive significant effect on the government bond's yield to maturity.